Low-temperature SnO2-modified TiO2 yields record efficiency for normal planar perovskite solar modules - Ding, Bin; Shi-Yu, Huang; Qian-Qian, Chu; Li, Yan; Cheng-Xin, Li; Chang-Jiu, Li; Guan-Jun, Yang (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Hybrid organic–inorganic perovskite solar cells (PSCs), particularly planar PSCs, have attracted significant attention because of their high efficiency, low fabrication costs, and simple preparation process. However, planar PSCs exhibit lower efficiency and stability than mesoporous PSCs primarily owing to defects in the electron transport layer (ETL). Herein, we introduced a SnO2 nanoparticle-modified TiO2 film (SnO2@TiO2) as an ETL. In addition, we proposed a simple three-step chemical bath method to achieve this SnO2@TiO2 structure at low temperatures (140 °C). The SnO2@TiO2 ETL significantly enhances electron extraction and decreases the trap states at the perovskite/ETL interface. We achieved average efficiencies of 21.27%, 19.79%, 17.21%, and 16.31% at the reverse scan and forward scan for the device areas of 0.10 cm2, 1.13 cm2, 5.25 cm2, and 10.56 cm2, respectively. Moreover, we achieved a certificated efficiency of 15.65% for a normal planar perovskite solar module with a masked area of 10.55 cm2. The SnO2@TiO2-based PSCs exhibit enhanced photocurrent and reduced hysteresis. Furthermore, the solar cell retained about 89% of its initial efficiency after about 750 hours of aging in dark and about 93% for 528 hours under full-sun illumination. Owing to the low-temperature processability and the absence of spin-coating steps, SnO2@TiO2 ETLs will provide a promising path for the commercialization of PSCs.